A Study on the Recycling of Aluminium Alloy 7075 Scrap - Ozer, Gokhan; Burgucu, Sarp; Marsoglu, Muzeyyen (CARL HANSER VERLAG, 2012)
Aluminium and its alloys have recently become an important metal whose area and amount of usage increase more and more, due to their mechanical properties, recycling ability, and penetrability. If it is considered that the bauxite, which is the raw material of aluminium is rare on earth, and also the area and amount of aluminium usage increases over time, the importance of aluminium recycling goes up. aluminium recycling has become crucial by means of both, the potential of the scrap's dependant increase on usage and the primary aluminium production, as it is providing energy and cost savings. 7xxx grades of scrap are collected with other scrap of aluminium alloys in one turn and recycled all together. As the regain of these alloys is not done by isolation oft he various grades, the finally recycled ingots result in lower grades. High value aluminium scrap is regrettably not recovered, as it was anticipated. This study is dealing with 7075 aluminium alloys originated from discharged blow molding tools and the rest piece cuttings of blocks and plates. The material has been subjected to an induction furnace, and has been remelted into small ingots and hardened according to 7075 aluminium alloy parameters (hardening aluminium tooling).
Keywords: Materials Science